2016
DOI: 10.1016/j.mcn.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced GABAA receptor alpha4 subunit plasticity involves phosphorylation and neuroactive steroids

Abstract: GABAA receptors containing α4 subunits are widely implicated in acute ethanol sensitivity, and their spatial and temporal regulation prominently contributes to ethanol-induced neuroplasticity in hippocampus and cortex. However, it is unknown if α4-containing GABAA receptors in the thalamus, an area of high α4 expression, display similar regulatory patterns following ethanol administration, and if so, by which molecular mechanisms. In the current study, thalamic GABAA receptor α4 subunit levels were increased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Additionally, PKA activation increases extrasynaptic α4 and δ subunit expression (Bohnsack et al, 2016). Similar mechanisms and regulatory phosphorylation patterns (PKCγ and PKCδ) have been also observed in thalamic GABA A R α4 subunit expression following acute and chronic EtOH administration where they are likely dependent on neuroactive steroids (Werner et al, 2016). …”
Section: 2 Gaba and Etoh Effectsmentioning
confidence: 66%
See 1 more Smart Citation
“…Additionally, PKA activation increases extrasynaptic α4 and δ subunit expression (Bohnsack et al, 2016). Similar mechanisms and regulatory phosphorylation patterns (PKCγ and PKCδ) have been also observed in thalamic GABA A R α4 subunit expression following acute and chronic EtOH administration where they are likely dependent on neuroactive steroids (Werner et al, 2016). …”
Section: 2 Gaba and Etoh Effectsmentioning
confidence: 66%
“…More recently, the Morrow laboratory has investigated two distinct populations of synaptic and extrasynaptic α4-containing GABA A Rs in cultured rat cortical neurons (Carlson et al, 2016a; Carlson et al, 2016b). They found that chronic EtOH treatment alters the abundance of both types of subunits, while six weeks of chronic EtOH diet, but not 2 weeks, increased mouse thalamic GABA A R α4 subunit levels (Werner et al, 2016). Chronic EtOH also decreased α1 mRNA and increased α6 mRNA in the cerebellum, and altered δ protein levels in the rat cerebellum and hippocampus (Mhatre and Ticku, 1994; Morrow et al, 1992).…”
Section: 2 Gaba and Etoh Effectsmentioning
confidence: 99%
“…The rapid down-regulation of extrasynaptic δ-GABA A Rs by a single EtOH withdrawal in present study is likely triggered by the increased interaction between δ-ICD and AP2-μ2 via PKCδ-mediated phosphorylation of μ2 regions in δ subunits. One previous study suggests a phosphorylation regulation of GABA A R-α4 subunits in the thalamus by PKCγ and PKCδ isoforms (Werner et al, 2016 ), however, it is unclear whether δ-ICD can be directly phosphorylated by PKCδ or other PKC isoforms. It would be important to test the functional significance of these μ2 binding sites within the ICD, as they potentially regulate the cell surface number of δ-GABA A Rs (Gonzalez et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Initially studies replicated data demonstrating that acute ethanol administration inhibited the spontaneous activity of medial septal neurons and then demonstrated that pretreatment with the 5α-reductase inhibitor finasteride completely blocked ethanol induced inhibition of medial septal neurons (VanDoren et al, 2000). Although finasteride can impact a variety of steroid hormones (Van Doren et al, 2000;Werner et al, 2016) the initial studies motivated investigations to determine if allopregnanolone directly alters hippocampal neurophysiology; it was reported that acute allopregnanolone administration dose dependently inhibited the spontaneous activity of hippocampal pyramidal neurons and that pretreatment with finasteride blocked ethanol induced inhibition of hippocampal pyramidal neurons . In addition, it was investigated if acute allopregananolone produced dose dependent impairments in hippocampal-dependent spatial memory in a manner similar to acute ethanol administration.…”
Section: Acute Alcohol and Cognition 24mentioning
confidence: 99%